The international community and the Caribbean : potential paths to achieving stability in development finance - Rambarran, Anston (Caribbean Centre for Monetary Studies [St. Augustine]TT, 2003)
Examines the contribution of the international community to supporting and financing Caribbean development, with a view towards identifying the possible engagement strategies for the future.